Acupuncture-induced changes of pressure pain threshold are mediated by segmental inhibition—a randomized controlled trial. Issue 11 (November 2015) - Baeumler, Petra I.; Fleckenstein, Johannes; Benedikt, Franziska; Bader, Julia; Irnich, Dominik
Abstract : Abstract: Our aim was to distinguish between spinal and supraspinal mechanisms in the intact nervous system by comparing homosegmental and heterosegmental effects of electroacupuncture (EA) and manual acupuncture (MA) on sensory perception in healthy volunteers by means of quantitative sensory testing. Seventy-two healthy volunteers were randomly assigned to receive either MA or EA at SP 6, SP 9, GB 39, and ST 36 at the left leg or relaxed for 30 minutes (control group [CG]). Blinded examiners assessed 13 sensory modalities (thermal and mechanical detection and pain thresholds) at the upper arms and lower legs before and after intervention by means of a standardized quantitative sensory testing battery. Change scores of all 13 sensory thresholds were compared between groups. The main outcome measure was the change score of the pressure pain threshold (PPT). There were no baseline differences between groups. Pressure pain threshold change scores at the lower left leg, in the same segment as the needling site, differed significantly ( P = 0.008) between the EA (median: 103.01 kPa) and CG groups (median: 0.00 kPa) but not between the MA (median: 0.00 kPa) and CG groups. No further significant change score differences were found between one of the acupuncture groups and the CG. The PPT can be changed by EA. The PPT increase was confined to the segment of needling, which indicates that it is mainly mediated by segmental inhibition in the spinal cord. This underscores the importance of segmental needling and electrical stimulation in clinical practice. Abstract : Supplemental Digital Content is Available in the Text.Electroacupucture increased pressure pain threshold in the segment of needling but not contralaterally or heterosegmentally, showing that this effect is mediated by segmental inhibition.